2004
DOI: 10.1161/01.cir.0000127812.62277.50
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Acutely Impaired Microvascular Reperfusion After Infarct Angioplasty With Magnetic Resonance Imaging

Abstract: Background-Despite the reopening of the infarct-related artery (IRA) with infarct angioplasty, complete microvascular reperfusion does not always ensue. Methods and Results-We performed cardiovascular MRI (CMR) in 20 acute myocardial infarction (AMI) patients within 24 hours of successful infarct angioplasty and 10 control patients without obstructive coronary artery disease on a clinical 1.5-T CMR scanner. Three-month follow-up CMR in AMI patients evaluated the impact of abnormal reperfusion on recovery of fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(101 citation statements)
references
References 34 publications
3
95
0
3
Order By: Relevance
“…Initial cine CMR sequences were performed in 3 standard long-axis (4-, 3-, and 2-chamber views) and short-axis slices (basal, mid, and apical), kept identical for each subsequent sequence throughout the CMR examination. 16 From an end-diastolic, 4-chamber, long-axis view, 5 equally spaced short-axis slices were planned, so that the 2 outer slices lined up exactly either with the tip of the apex or the mitral annulus. The 2 outer slices were then deleted, leaving 3 slices corresponding to typical basal, mid, and apical short-axis views.…”
Section: Cmr Protocolmentioning
confidence: 99%
“…Initial cine CMR sequences were performed in 3 standard long-axis (4-, 3-, and 2-chamber views) and short-axis slices (basal, mid, and apical), kept identical for each subsequent sequence throughout the CMR examination. 16 From an end-diastolic, 4-chamber, long-axis view, 5 equally spaced short-axis slices were planned, so that the 2 outer slices lined up exactly either with the tip of the apex or the mitral annulus. The 2 outer slices were then deleted, leaving 3 slices corresponding to typical basal, mid, and apical short-axis views.…”
Section: Cmr Protocolmentioning
confidence: 99%
“…Kim et al questioned whether there is a correlation between delayed contrast enhancement and the age of myocardial infarction, as well as the use of CMR to detect viability and irreversible lesions and evaluate the contractile function of the myocardium. [21][22][23][24] The theory was tested on canine models, and their results revealed that in the first 24 hours from the infarction, hyperenhancement occurs both in the necrosis zone and at the borderline that includes the hibernating myocardium. In terms of chronic infarction, the contrast agent has a strict affinity for the fibrosis area, and the imaging delineation of the hibernated myocardium from the necrosis area is a real challenge.…”
Section: Clinical Applications Of Cmrmentioning
confidence: 99%
“…It may manifest at the time of PCI as persistent STelevation and coronary 'no-reflow' i.e TIMI flow ≤2 as defined by the Thrombolysis in Myocardial Infarction (TIMI) blood flow grade scale, used to evaluate the quality of coronary flow during coronary angiography [111,112]. The presence of the no-reflow phenomenon indicates a microvascular obstruction and its presence in reperfused STEMI patients, as visualised eg by cardiac magnetic resonance imaging (CMR), is associated with larger infarct size, worse LV ejection fraction, adverse LV remodelling as well as unfavorable short and long term outcomes [113][114][115][116].…”
Section: General Aspectsmentioning
confidence: 99%